Analysis of Word Formation Process In Online Advertisements - Friska Olivia Panggabean (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2024)
This thesis aims at finding the types of word formation process in online advertisements and analysing how those types are used. The data source was obtained from the official shampoo advertising websites and YouTube during 2020. It used a descriptive qualitative method by applying the theory of word ordering proposed by several linguistic experts namely O'Grady and Guzman (1996), and Hatch and Brown (1995). From the analysis conducted, the researcher found 9 out of 12 existing word ordering processes including compounding, borrowing, initialization, clipping, back formation, inflection, derivation, and clitization. Among all, the words found within the scope are words formed through the process of compounding, derivation and borrowing. However, the words formed through the process of coinage, acronyms, and onomatopoeia were not found. In addition, the results of the analysis also showed that the words used in the advertisements are catchy and serve to explain the description and the function of the products.